Vegetarian diet for children-practical guidelines - Rok Orel (Zdravniški Vestnik, 2014)
Paediatric profession recommends that infants, children and adolescents should have a balanced, mixed diet containing nutrients of plant and animal origin. Paediatricians are sometimes faced with children who are fed a vegetarian diet in which certain types of foods are excluded. The avoidance of all foods of animal origin (meat, fish, eggs, milk and honey in vegans, raw eaters and fruitarians) poses a serious risk due to the lack of several nutrients: iron, zinc, calcium, iodine, vitamins B12, B2, A, D, n-3 fatty acids, particularly docosahexaenoic acid (DHA, C22: 6ω-3), proteins and energy. The article provides an overview of critical nutrients in the diet of vegetarians, the list of laboratory investigations that need to be carried out for determination of specific nutrient deficiencies, and practical recommendations for vegetarian diet in children.